RETROSPECTIVE ANALYSIS OF ACHIEVEMENTS OF WOMEN WEIGHTLIFTERS AT THE OLYMPIC GAMES - V. Panayotov; N. Yankova (Trakia Journal of Sciences)
PURPOSE: Women’s Olympic weightlifting became a part of the program of the Olympic Games at the 2000 Olympics in Sydney, Australia. The Bulgarian weightlifting school has been very successful in preparing elite female weightlifters since its very introduction. This review aimed to assess and rank the results of the Bulgarian female weightlifters at the Olympic Games held between 2000 and 2016. METHODS: Rankings of the Bulgarian female weightlifters at the Olympic Games were analyzed and compared by both absolute weight and values corrected by the Sinclair coefficient. RESULTS: A positive trend in results for both competitive movements was found. Results in the clean and jerk were better on average than those in the snatch. We consider the higher performances of female weightlifters measured in the weight class of 69 kg as an indicator of evolution in their results during recent years. CONCLUSIONS: The Bulgarian school in women’s Olympic weightlifting established a tradition in preparing elite weightlifters during the last 18 years. To preserve this positive trend, coaches should base the sports selection process for young female weightlifters on scientific grounds.